PURSED LIPS BREATHING (MENIUP BALON) EFEKTIF MENINGKATKAN OKSIGENASI PADA PASIEN ANAK DENGAN BRONKOPNEUMONIA DI RS HERMINA BEKASI - Ardita Yulia Pramest; Sri Laela (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2024)
Abstract Bronchopneumonia, also known as lobar pneumonia, is inflammation of the lung tissue which usually affects the bronchi, alveoli and surrounding areas, caused by infectious agents such as bacteria, viruses, fungi and aspiration of foreign objects which can cause death. One of the appropriate nursing treatments for cases of bronchopneumonia in children is pursed lips breathing therapy. Pursed lips breathing is a deep breathing exercise with a modification of blowing up a balloon. The aim of this study was to determine the effectiveness of pursed lips breathing (blowing a balloon) on oxygenation status in pediatric patients with bronchopneumonia at Hermina Bekasi Hospital. The methodology used is a case study with data collection techniques, namely interviews, observation, physical examination and documentation, carried out in the Children's Care Room at Hermina Hospital Bekasi on 14 -16 May 2024. After carrying out the pursed lips breathing technique for 3 days, it was found that the patient's oxygenation had improved; breathing from 32x/minute to 24x/minute, oxygen saturation from 96% to 99% and no shortness of breath. Pursed lips breathing in Bronchopneumonia patients is able to overcome shortness of breath, increase oxygen saturation, reduce additional breath sounds and sputum in the patient's airway. It is hoped that patients and families can prevent recurrent bronchopneumonia by adopting a clean and healthy lifestyle, carrying out re-controls to monitor the progress of the disease and applying the pursed lips breathing technique to improve oxygenation status in children.